2013
DOI: 10.9775/kvfd.2012.8369
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Graded Levels of Crude Glycerine Addition to Diets on Growth Performance, Carcass Traits and Economic Efficiency in Broiler Chickens

Abstract: The aim of the current study was to evaluate the effects of graded levels of crude glycerine addition to diets on growth and economic performance, carcass yield, organ weights and moisture levels of meat in broiler chickens. For this purpose, a total of 270 one day old male chicks (Ross 308) were randomly divided into 3 equal groups which fed with isocaloric and isonitrogenous diets with graded levels (0%, 5% and 10%, respectively) of crude glycerine. Each of experiment group was constituted by 5 subgroups wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Valores aproximados foram encontrados por (FREITAS et al, 2017;SEHU et al, 2013;SILVA et al, 2017;2019) que observaram que a inclusão de até 3% de glicerina não afetou cor, forma e estrutura do fígado das aves. Dessa forma, pode-se inferir que os que os níveis de glicerina utilizados nas dietas não interferiram nas características produtivas e na qualidade física da carne do peito de frangos de corte aos 42 dias de idade.…”
Section: Resultsunclassified
“…Valores aproximados foram encontrados por (FREITAS et al, 2017;SEHU et al, 2013;SILVA et al, 2017;2019) que observaram que a inclusão de até 3% de glicerina não afetou cor, forma e estrutura do fígado das aves. Dessa forma, pode-se inferir que os que os níveis de glicerina utilizados nas dietas não interferiram nas características produtivas e na qualidade física da carne do peito de frangos de corte aos 42 dias de idade.…”
Section: Resultsunclassified
“…Cerrate et al (2006) assured that glycerol had no significant effect on broiler BWG. Contrarily, Sehu et al (2013) found that glycerine had significant impact on broiler chicken BWG and connected it with AME n content in glycerine which is 10% higher than maize. Bernardino et al (2015) suggested that these differences might be due to dissimilarities in energy content and other substances present in glycerine like methanol.…”
Section: Growth Performancementioning
confidence: 97%
“…Studies using glycerin in broiler diets have shown that its inclusion does not affect the main performance characteristics at different production stages (Cerrate et al, 2006;Sehu et al, 2013;Silva et al, 2012). In studies conducted to evaluate the effects of increasing levels of glycerin (0, 5, and 10%) in diets of broilers from 1 to 42 days of age, Sehu et al (2012Sehu et al ( , 2013 observed that the inclusion of up to 5% glycerin did not affect performance traits, carcass yield, or body weight. Similarly, Romano et al Purified glycerin in balanced diets of broiler chickens treated from 1 to 42 days of age Silva et al (2014), using diets containing 2.5, 5.0, 7.5, and 10% glycerin, concluded that broilers can adequately metabolize up to 7.5% of dietary glycerol.…”
Section: Introductionmentioning
confidence: 99%